Physiological Evaluation of Some Fertility Hormones for Women with Polycystic Ovary Syndrome in Wasit Province - Sfaieh, Aqdas Mohammed (Journal of Science in Medicine and Life, 2024)
Polycystic ovary syndrome (PCOS) is the most common metabolic and endocrine disturbance affecting about (15%) of female in reproductive age, it is the most common causes of infertility, recognized by hirsutism, anovulation problems and hyperandrogenemia problems. The aim of this study was to estimate the concentration of serum luteinizing hormone LH, follicle stimulating hormone FSH, LH/FSH Ratio, testosterone, dehydroepiandrosterone sulfate DHEA-S , and serum prolactin hormones for women diagnosed with PCOS and healthy women of the control group. The role of this study included 70 women in reproductive age diagnosed with PCOS, were divided into two groups; 40 married women (57.14%) and 30 unmarried women (42.85%), age range (18-45) years, this study was done in Al-Zahraa Teaching Hospital, AL Kut city, Wasit province, from January, 2024 to may, 2024. While, the control subject included 50 women with regular menstrual cycle and with no any hormonal problems, the control individuals were closely as the same ages as the patients group. The obtained results indicated that the concentrations of serum LH, LH/FSH Ratio, testosterone hormone, and dehydroepiandrosterone sulfate significantly elevated (p≤0.05) in women with (PCOS) compered with control groups for all age ranges. On the other hand , no significant variations (P>0.05) were notice in the mean values of serum follicle stimulating hormone between polycystic ovarian syndrome women group and control group in all age ranges. While, serum prolactin hormone considerably significant increased (p≤ 0.05) in married women having (PCOS) as compered with control subjects. Whereas, no significant variations (p˃0.05) were recorded in serum prolactin level in unmarried women having (PCOS) than in control group for all age ranges. Conclusion: This study concluded that there were elevated levels in all hormones including serum LH, LH/FSH Ratio, testosterone hormone, and (DHEA-S) were found in patients women having polycystic ovarian syndrome as compered with control groups for all age ranges, except the level of follicle stimulating hormone was showed no significant differences than in control group. Also, an increase in these hormone levels may be associated with increased serum prolactin hormone in married women which may be an important indicator for increase the infertility for women having PCOS.